The role of visualization in data-based decision-making: comparative analysis of the experience of the mass media of Kazakhstan and China (Herald of Journalism, 2023)
With the development of visualization, data-driven decision making has accelerated. The new simple and easy to understand format has made publications more effective, while influencing people's minds through visual forms. The average user of the global network in a matter of seconds can study and analyze information of any tone, regardless of the level of complexity. In this work, we studied the impact of visualized journalistic materials on the audience in the cultures of Kazakhstan and China, whose level and sources of viewing are fundamentally different.The purpose of the study is to demonstrate various ways of transforming text messages into custom-designed visualization and the effectiveness of visualization for data-driven decision making in the media of Kazakhstan and China.Research methodology: the content analysis method was used to identify the tools, techniques and experience of using visualization in the media of Kazakhstan and China. Comparative analysis has proven earlier, frequent and technically more relevant use of information visualization in the Chinese media than in Kazakhstan.Research results. The visualization of big data in the print and electronic media of Kazakhstan and China contributes to the rapid and efficient presentation of information, which helps the audience quickly analyze facts and make decisions, which contributes to the growth of the economies of both countries. Various types of charts, graphs, tables, color schemes should be selected according to the nature of the content of the message. The interactivity of visualization helps to increase the involvement of the audience - the function of social exchange for the dissemination and exchange of information is implemented.Practical value. The results of the study can be used in the training of future journalists as materials on specialized and elective disciplines. The work can serve as a theoretical and practical basis for media research.Key words: information, visualization, big data, journalism, mass media.